Landscape of the Peripheral Immune Response Induced by Local Microwave Ablation in Patients with Breast Cancer. Issue 17 (11th April 2022) - Zhou, Wenbin; Yu, Muxin; Mao, Xinrui; Pan, Hong; Tang, Xinyu; Wang, Ji; Che, Nan; Xie, Hui; Ling, Lijun; Zhao, Yi; Liu, Xiaoan; Wang, Cong; et al.
Abstract: Minimally invasive thermal therapies have been attempted in the treatment of breast cancer, and the immune response induced by these therapies has not been fully reported. A clinical trial is performed to determine the effect of microwave ablation (MWA) in the treatment of early‐stage breast cancer. The authors perform single‐cell RNA sequencing on peripheral blood mononuclear cells (PBMCs) from six patients before and after ablation. NK and CD8 + T cells are activated by MWA of breast cancer, with the increased inhibitory signature of CD8 + T cells but not dysfunctional. Enhanced co‐stimulatory signature of CD4 + T cells is observed and increased frequency of ICOS + CD4 + T cells after MWA is confirmed by flow cytometric analysis. After ablation, T‐cell clones expand with increased T‐cell receptor diversities. Activated antigen receptor‐mediated signaling pathways are found in B cells. Enhanced interactions between B cells and CD4 + T cells are found, indicating that B cells are important antigen‐presenting cells that initiate CD4 + T cells in MWA‐induced immune response. Blockade of CTLA‐4 or PD‐1 of post‐MWA PBMCs show higher T‐cell activity than that of pre‐MWA PBMCs. This study provide global characteristics of MWA‐induced systemic immune response and pave a way for the identification of potential targets to improve the immune response. Abstract : This study finds that peripheral NK and T cells are activated by MWA of breast cancer partly dependent on B cell and CD4 + T cell collaboration, and MWA combined with immune checkpoint inhibitor may be a promising strategy for the treatment of early‐stage breast cancer.